Differentiated Learning to Facilitate Interest in Mathematics Learning in Elementary School - Pariang Sonang Siregar; Firman Santosa; Shindy Lestari; Rindi Genesa Hatika (MIMBAR PGSD Undiksha, 2026)
Low interest in mathematics among elementary students affects the optimization of their learning outcomes and mathematical skills. This condition requires learning that accommodates diverse student characteristics, including differentiated instruction. This study aims to analyze students’ responses to the implementation of differentiated learning in improving interest in learning mathematics. The study employed a mixed methods approach with a convergent parallel design, which simultaneously integrated quantitative and qualitative data. The research subjects involved 25 elementary school students. Quantitative data were collected through a mathematics learning interest questionnaire based on differentiated learning, while qualitative data were obtained through in depth interviews with student representatives based on gender, mathematical cognitive level, learning interest, and learning style. Quantitative data were analyzed using one way ANOVA, while qualitative data were analyzed through thematic analysis. The results showed that the implementation of differentiated learning had a significant effect on increasing students’ interest in learning mathematics. The qualitative findings strengthen the results by showing students’ positive responses to learning adapted to their needs, characteristics, and learning preferences. This study concludes that differentiated instruction creates more meaningful, adaptive, and inclusive mathematics learning while supporting students’ mathematical knowledge and skills. The implication is that teachers need to design flexible, student-centered, and responsive learning to address diverse learning needs.